Increased MLKL mRNA level in the PBMCs is correlated with autoantibody production, renal involvement, and SLE disease activity - Mingjiao Zhang; Hongyu Jie; Yong Wu; Xinai Han; Xing Li; Yi He; Xingliang Shi; Yuwei Luo; Ying Sun; Jinlong Yang; Jing Yang; Shulv Quan; et al. (Arthritis Research & Therapy, 2020)
Abstract Background Necroptosis is a form of regulated necrosis that is involved in various autoimmune diseases. Mixed lineage kinase domain-like pseudokinase (MLKL) has been identified as a key executor of necroptosis; however, the significance of MLKL in peripheral blood mononuclear cells (PBMCs) of systemic lupus erythematosus (SLE) has not been investigated. In this study, we aimed to determine the mRNA level of MLKL in PBMCs and examine its relationship with clinical features and serological parameters in SLE. Methods Real-time transcription-polymerase chain reaction (RT-PCR) analysis was used to determine the expression of MLKL mRNA in PBMCs from 59 patients with SLE, 25 patients with rheumatoid arthritis (RA), and 30 age- and sex-matched healthy controls (HC). Spearman’s correlation test was performed to assess the correlation of MLKL mRNA with clinical variables. The receiver operating characteristic (ROC) curve was created to evaluate the diagnostic value. Results Our results showed MLKL mRNA in PBMCs was upregulated in SLE patients compared to that in RA and HC individuals. SLE patients positive for antinuclear antibodies had significantly higher MLKL mRNA than antibody-negative patients. In SLE patients, MLKL mRNA was found to be upregulated in patients with lupus nephritis (LN) as compared with patients without LN, and also higher in active patients than in stable patients. MLKL mRNA level was significantly and positively correlated with c-reaction protein (CRP) (r = 0.3577, p = 0.0237), erythrocyte sedimentation rate (ESR) (r = 0.4091, p = 0.0043), serum immunoglobulin G (IgG) concentration (r = 0.3546, p = 0.0289), and the numbers of positive antinuclear antibodies (ANAs) (r = 0.3945, p = 0.0432). ROC analysis showed that MLKL mRNA in PBMCs had an area under the curve of 0.9277 (95% CI 0.8779–0.9775, p < 0.001) to discriminate SLE from controls. Conclusions These results suggest that increased MLKL mRNA level in the PBMCs of SLE patients is correlated with renal involvement and disease activity, identifying a subgroup of patients with SLE or LN who may benefit from early diagnosis and therapies targeting MLKL.